GOLD-SULFIDE MINERALIZATION OF QUARTZ VEINS IN GRANITES OF THE SOUTH SUKHTELYA GOLD OCCURRENCE (SOUTH URALS) - S.I. Bryukhov; D.A. Artem’yev; I.A. Blinov; N.R. Ayupova; A.S. Tseluyko (Минералогия)
The paper considers mineralogical and geochemical features of gold-sulfide mineralization of quartz veins in granites of the Katsbakh complex in the South Sukhtelya gold occurrence (South Urals). The sulfide content of quartz veins varies from 1 to 3 vol. %, rarely reaching 10 vol. %, and the average Au content is 5–10 g/t. Three types of native gold are identified: 1) in assemblage with Fe oxyhydroxides and in quartz (the fineness of 649–830 ‰), 2) in assemblage with tourmaline (the fineness of 870–888 ‰) and 3) in Fe oxyhydroxides in assemblage with fischesserite and in secondary Cu minerals. The sulfides include pyrite, chalcopyrite, sphalerite and galena. Pyrite is enriched in Ni, chalcopyrite contains Ag, Sn, and Sb, galena is rich in Se, Ag, Te, Bi, and Sb, and sphalerite has a higher amount of Cd, In, and Hg. The Au content of pyrite, chalcopyrite, and sphalerite is less than 0.1 ppm increasing up to 5 ppm in chalcocite and up to 168 ppm in Fe hydroxides. The ores formed during a gradual temperature decrease in a range from 400 to 200 °C, which corresponds to a sequence of mineral formation: pyrite → chalcopyrite → sphalerite → galena. The oxidation of sulfides resulted in the formation of the high-fineness native gold in assemblage with fishesserite.